Clinical utility of different anti-Müllerian hormone – AMH assays for the purpose of pregnancy prediction. (3rd October 2017) - Liss, Joanna; Kunicki, Michal; Czyzyk, Adam; Pastuszek, Ewa; Zabielska, Judyta; Meczekalski, Blazej; Lukaszuk, Krzysztof
Abstract: Purpose : Comparison of outcomes of IVF cycles where the AMH levels was measured with five different AMH kits: Immunotech (IOT), Beckman Coulter II Gen. RUO, Beckman Coulter II Gen. IVD (BC II IVD), Ansh Labs ultrasensitive (Ansh) and the automated Elecsys Roche assay. Methods : Retrospective analysis of clinical data for 3693 cycles. Results : In women < 35 years with low (<0.6 ng/ml) and high (>1.4 ng/ml) AMH concentrations, and in those > 39 years with medium (≥0.6 and ≤1.4 ng/ml) and high AMH concentrations the clinical pregnancy rate differed significantly among groups of patients whose AMH level was measured with different kits. In those subgroups, the highest rates were recorded for the BC II IVD and Ansh groups, while the lowest in the IOT group. AMH concentrations differed significantly between different kits in all age groups (the highest in each age group was for the IOT kit and the lowest for BC II IVD). AMH correlates positively with antral follicle count, MII and number of oocytes retrieved. Conclusions : This study demonstrated that we could expect very different pregnancy rates with the same AMH results depending on the AMH kit used. That would means, different values of AMH could similarly lead to misleading clinical decisions in IVF.